Evaluation of the mechanical properties of Composite Resins Treated with Royal Jelly, Glycerin, and Panavia Oxyguard used as Oxygen-Inhibiting Agents – an in vitro study (Asian Journal of Pharmaceutics (AJP), 2025)
To compare and contrast the efficacy of Royal Jelly, Glycerine, and Panavia Oxyguard as oxygen-inhibitors with respect to degree of conversion, surface hardness, and surface irregularity of composite resins.Methods: With the selection of such one resin composite having the name Tetric-N-Ceram, A2 shade, thirty discsof composite was fabricated. In these thirty discs, oxygen- inhibiting agents were applied before light curing forthe three groups (10 each) as follows: group A-glycerine, group B-Panavia Oxyguard, and group C-Royal Jelly.Surface hardness was measured by using a Vickers micro-hardness tester, surface roughness was assessed througha 3D profilometer, and degree of conversion was calculated by Fourier-transform infrared (FTIR) spectroscopy.Results: Highest surface hardness (mean: 58.34 VHN) was revealed in specimens treated with Royal Jelly,followed by Glycerine (37.77 VHN) and then Panavia Oxyguard (30.02 VHN). Royal Jelly also exhibited superiorperformance in aspects of surface characteristics and degree of conversion again showing better polymerizationof the natural agents than the synthetic ones. Conclusion: Royal Jelly shown to be an effective oxygen-inhibitorin that it exhibits improved polymerization, surface hardness, and total quality of surface of the composite resinswhen compared with Glycerine and Panavia Oxyguard. The bioactive features that it possesses also give credenceto its potential as a natural alternative in restorative dentistry